"Philosophy of War" in Non-Western Intellectual Traditions: the Experience of the Indigenous Population of North America and China - Sergii Rudenko; Yaroslav Sobolievskyi (International Society of Philosophy and Cosmology, 2022)
There is a special relationship to the phenomenon of "war" in the history of philosophy, political science, cultural studies, and other humanitarian disciplines. War has always been an integral part of history, politics, religion, and culture despite its destructive power and inhuman consequences. In modern philosophy, there is a very controversial concept - "philosophy of war," which is considered by some intellectuals to be a special part of the philosophy of politics, while others, on the contrary, deny the existence of this phenomenon. In an attempt to study this phenomenon from the outside, in this article, the authors deliberately set themselves the task of analysing the main ideas of the "philosophy of war" in non-Western intellectual traditions, such as geographically opposed China and the Indigenous peoples of North America. In these intellectual cultures and philosophical traditions, there are basic ideas, in comparison to which it is possible to outline special points of contact. For example, the peaceloving indigenous peoples of North America, whose history is not devoid of bloody events, did not know such a large-scale phenomenon of war, similar to Western history. However, in spiritual culture, we find evidence of reflection on military events, such as military poetry, the purpose of which is to sing of virtues. For the Chinese philosophy of war, these themes are deeply rooted. Military-political treatises have always been an integral part of China's spiritual tradition.